Producing quality seedlings of Bougainvillea - Jain, Ritu; Tiwari, Ajay; Kumar, Prabhat; Singh, Babita (Indian Horticulture, 2019)
Bougainvillea is one of the highly suitable plant for controlling air pollution as it is quite hardy in nature and has capability to absorb gases as well as providing platform to accumulate the SPM. It is most commonly propagated by hardwood cuttings which primarily depend on season, stage of maturity and varieties used. Conventional propagation methods are slow and require a large number of mother plants and their permanent maintenance, blocking precious production space. In certain varieties, rooting percentage is so low that by multiplying through conventional methods, it is not possible to meet the demand. Since, tissue culture is a useful tool for successful multiplication of vegetatively propagated shrubs in order to get uniform, true-to-type and disease free, quality planting material, therefore efforts were made to standardize the protocol for mass multiplication of bougainvillea.